Geographical variation in morphological leaf traits of Huperzia serrata (lycopodiaceae) from Vietnam - Minh, Nguyen Thi Ai; Trieu, Le Ngoc; Duy, Nong Van; Tien, Tran Van (Academia Journal of Biology, 2019)
Morphological leaf traits can be used to assess adaptive responses of plants to environmental conditions. To assess how the representation of Huperzia serrata leaf traits, such as leaf length (LL), leaf width (LW) and leaf area (LA) response to changes in mean annual temperature (MAT), sunshine duration (SuH), mean annual precipitation (MAP), air humidity (Hu), intraspecific variation of the morphological leaf traits of the species was analyzed along a geographical gradient of Vietnam. The results showed that among the three populations at the three sites, leaf sizes increased with MAT and MAP. Huperzia serrata, climatic factors, morphological leaf traits, Vietnam.